Purifikasi Inhibitor Atpase/Rna Helikase Virus Japanese Encephalitis Dari Streptomyces chartreusis - Elfita, Lina; Ratnakomala, Shanti; Suryadi, Herman; Lisdiyanti, Puspita; Utama, Andi (Majalah Ilmu Kefarmasian, 2009)
Japanese encephalitis virus (JEV) is a neuropathogenic virus commonly caused cen-tral nervous diseases such as meningitis and severe encephalitis. Although vaccine has been developed, no specific and effective drug is available so far. We previously carried out a screening of inhibitor of JEV RNA helicase, an enzyme that essential for virus replication, from Actinomycetes and found that Streptomyces chartreusis produce the inhibitor of JEV RNA helicase. In this study, an extracellular protein which has inhibition activity on ATPase activity of JEV RNA helicase was purified from supernatant of Streptomyces chartreusis culture by ammonium sulfate pre-cipitation and size exclusion chromatography. SDS-PAGE analysis showed a single band with aproximate molecular mass of 11,4 kDa, suggesting that the inhibitor was successfully purified into a single protein.